Pro-Contradictions and Harmony of Sholawat Wahidiyah in Islamic Multicultural Education in Tenggeles Village - Siti Rohatul Asroriyah; Muhammad Miftah; Nur Sa'id; Bayu Saputra Rahma Wijaya; Muhammad Hakim Ashlih Rosyada (Rumah Moderasi Beragama of UIN Siber Syekh Nurjati Cirebon, 2025)
This research aims to explore the content and practice of Islamic multicultural education in Tenggeles Village through a focus on peaceful co-existence among Nahdlatul Ulama (NU) members and Wahidiyah Sholawat practitioners. A descriptive qualitative approach is used here through observation, indepth interviews among religious and community officials as well as documentations of religious activities as well as social activities. The results show that peaceful co-existence is made possible even amid ritual disparities as a result of strategic positioning of religious officials as facilitators of dialogue as well as tolerance builders through their own practice. Multicultural education within the village grows organically as part of daily activity such as recitation of Qur’an, tahlil as well as khatmil Qur’an that impart values of tolerance (tasamuh) and brotherhood (ukhuwah) in young people. Social cohesion is expressed through communal activities such as fund contributions to funeral ceremonies as well as support to orphans as well as commemorative activities of national significance. Tenggeles illustrates that controversies that revolve around Wahidiyah that are waged in parts of a country do not apply universally as a result of overwhelming impact a flexible and accommodative village-based socio-cultural setting provides to outright acceptance. This work contributes to “effective passive tolerance” as a hypothetical formulation that is defined as mutual regard of difference without requiring assimilation yet building strong social cooperation. As a result, Islamic multicultural education can organically internalize itself into community activity without depending on institutional frameworks.